Vegetative swale for treatment of stormwater runoff from construction site - Ismail, A.F. (Universiti Putra Malaysia Press, 2014)
Land development, especially construction works, increase storm water volumes and pollution loads into rivers and lakes. The temporary drainage system at construction sites, particularly during the construction stage discharges a large amount of pollutants that can damage the aquatic system of the receiving water bodies. The potential of vegetative swale to alleviate this problem was evaluated. The size of the constructed vegetative swale was 7cm deep, 400cm long and 15cm wide at the bottom, and 17cm wide at the top. The experiment was conducted batch wise by filling the storage tank with the run-off water from the construction site. The water was allowed to flow through a pipe into the retention basin to maintain uniform flow before it entered the swale. The study showed that the run-off infiltrated through the soil at a rate of 489.6 mm/hr. Samples of surface run-off and infiltration water were collected at the end and the bottom of the swale. The results indicate that chemical oxygen demand (COD), total suspended solid (TSS), turbidity, iron and zinc were reduced by 85.4, 80.8, 36.4, 52.8 and 96.0, respectively, by surface flow and 91.1, 98.8, 58.2 55.5 and 98.1, respectively, by infiltration. Removal of nitrate and phosphorus by the planted vegetation was 69.4 and 21.1, respectively, by infiltration. However, nutrient removal by surface flow was negligible. In conclusion, the vegetative swale was able to improve the water quality of the storm water run-off from the construction site from Class V to Class III, according to the Interim National Water Quality Standards for Malaysia. Â© 2014 Universiti Putra Malaysia Press.